A Literacy of Armed Love: Confrontation and Desire in Aesthetic and Critical Projects - Anne E. Crampton (Studies in Social Justice, 2019)
The article argues that creative confrontations with damaging discourses as part of a critical literacy curriculum can be viewed as acts of love, for self and community. Using data from a multi-sited critical ethnography, the study considers the literacy productions of two focal students in diverse schools, a charter middle school and a large urban high school. Mediated discourse analysis of their work explores their aesthetic and critical literacy productions as refusals of oppressive discourses pressing against marginalized identities, and as expressions of desire for imagined, better realities. This research views such performances of multimodal creative resistance as an audacious literacy of desire, valuable as standards-meeting persuasive compositions, but also immeasurably valuable because of the emotional experience of the student producers, who were powerfully affected through the twin pleasures of resisting and imagining. This study illustrates how literacy projects might both inhabit and move forward Freire’s concept of armed love.